PREVALENSI JENIS NYERI KEPALA PRIMER (MIGRAINE, TENSION TYPE HEADACHE, CLUSTER HEADACHE) PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA ANGKATAN 2022 - Payung, Dicky Julistyo; Huwae, Laura B.S.; Ruspanah, Ivanmorl; Silalahi, Parningotan Yosi; de Lima, Filda V.I.; Nikijuluw, Enseline (Molucca Medica, 2024)
Primary headache (NKP) is the most common neurological complaint among medical students due to overexposure to physical (deprived sleep and unhealthy eating) and psychosocial stresors such as stres, anxiety and depression. The majority of these headaches can be caused by a primary disorder or an acute illness which is generally harmless. But in some cases, headaches can be the first symptom of a neurological disorder that can threaten a person's life. This study aims to determine the prevalence of primary headache in students of the Faculty of Medicine, University of Pattimurqa class of 2022. This research is a descriptive research type with a cross-sectional design using primary data, where primary headache will be assessed by the Headache Intake Questionnaire, Cleveland Clinic Canada. The results of the research conducted showed that out of a total of 225 students, 84,44% (190 people) experienced primary headaches. The results of this study also found that the most common type of primary headache experienced by students in class 2022 was migraine with a percentage of 55.27% (105 people).